STUDENTS’ PHONEMIC AWARENESS IN MASTERY ENGLISH VOWEL AND CONSONANT SOUNDS - Harahap, Yunita Mutiara; Rahmawati, Wiki Tedi (FKIP Universitas Al Washliyah Medan, 2024)
This research dealt with the students’ phonemic awareness in mastery English vowels and consonants sounds. The aim was to show activities carried out by the students to pronounce the English vowels and consonants sounds and to read as well as to write the sounds symbol in phonemic transcription. The subject in this research was the second semester students of English Education Study Program of a private university in Medan with total number of 15 students. Descriptive qualitative with observation was designed to implement this research. The subject of this research was observed thoroughly during the learning process. The result showed that the students were aware of phonemic in English sounds. They were able to understand the phonemic concept of English vowels and consonants sounds. They were able to pronounce and differentiate the phonemic transcription of English vowel and consonant sounds.